2017
DOI: 10.1111/acer.13338
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Epigenetic Mechanisms in Alcohol Addiction

Abstract: Alcohol use disorder (AUD) is a complex brain disorder with an array of persistent behavioral and neurochemical manifestations. Both genetic and environmental factors are known to contribute to the development of AUD, and recent studies on alcohol exposure and subsequent changes in gene expression suggest the importance of epigenetic mechanisms. In particular, histone modifications and DNA methylation have emerged as important regulators of gene expression and associated phenotypes of AUD. Given the therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 172 publications
(257 reference statements)
0
79
0
Order By: Relevance
“…It is possible that binge alcohol changed the expression levels of trophic factors in the brain, for instance, BDNF, GDNF, and EGF are all important for neurogenesis and are affected by alcohol (Janak et al, ). Additionally, it is possible that alcohol is affecting neurogenesis via epigenetic mechanisms (see Berkel & Pandey, for review). One study found reduced methylation of the CpG (Cytosin‐phosphatidyl‐Guanin) of the promoter of NGF in the serum of alcohol dependent patients (Heberlein et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that binge alcohol changed the expression levels of trophic factors in the brain, for instance, BDNF, GDNF, and EGF are all important for neurogenesis and are affected by alcohol (Janak et al, ). Additionally, it is possible that alcohol is affecting neurogenesis via epigenetic mechanisms (see Berkel & Pandey, for review). One study found reduced methylation of the CpG (Cytosin‐phosphatidyl‐Guanin) of the promoter of NGF in the serum of alcohol dependent patients (Heberlein et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genome-wide association studies (GWAS) have identified the genomic region encompassing the histone demethylase KDM4C gene as a hotspot associated with alcohol withdrawal symptoms (Wang et al, 2012). As research into the negative affective states seen during alcohol withdrawal and addiction continues, additional epigenetic modifications such as histone methylation, phosphorylation, and others may emerge as novel biomarkers of alcohol-induced anxiety in brain circuits such as the amygdala (Krishnan et al, 2014; Berkel and Pandey, 2017). …”
Section: Chronic Alcohol Exposure-induced Withdrawal Is Anxiogenicmentioning
confidence: 99%
“…As many of the associated articles have reported, acute, chronic and intermittent exposures to alcohol have substantial epigenetic effects (see e.g. Berkel and Pandey 2017; Lopez-Moreno et al 2015). While the breadth of epigenetic changes in synaptic function remain to be completely determined, changes in genes e.g.…”
Section: Discussionmentioning
confidence: 99%